Eustatic control of late Quaternary sea-level change in the Arabian/Persian Gulf. Issue 1 (July 2014) - Stevens, Thomas; Jestico, Matthew J.; Evans, Graham; Kirkham, Anthony
Abstract: Accurate sea-level reconstruction is critical in understanding the drivers of coastal evolution. Inliers of shallow marine limestone and aeolianite are exposed as zeugen (carbonate-capped erosional remnants) on the southern coast of the Arabian/Persian Gulf. These have generally been accepted as evidence of a eustatically driven, last-interglacial relative sea-level highstand preceded by a penultimate glacial-age lowstand. Instead, recent optically stimulated luminescence (OSL) dating suggests a last glacial age for these deposits, requiring >100 m of uplift since the last glacial maximum in order to keep pace with eustatic sea-level rise and implying the need for a wholesale revision of tectonic, stratigraphic and sea-level histories of the Gulf. These two hypotheses have radically different implications for regional neotectonics and land–sea distribution histories. Here we test these hypotheses using OSL dating of the zeugen formations. These new ages are remarkably consistent with earlier interpretations of the formations being last interglacial or older in age, showing that tectonic movements are negligible and eustatic sea-level variations are responsible for local sea-level changes in the Gulf. The cause of the large age differences between recent studies is unclear, although it appears related to large differences in the measured accumulated dose in different OSL samples.